Transcranial Motor-Evoked Potentials Are More Readily Acquired Than Somatosensory-Evoked Potentials in Children Younger Than 6 Years. (January 2016) - McIntyre, Ian W.; Francis, Lisa; McAuliffe, John J.
Abstract : BACKGROUND: There is a general belief that somatosensory-evoked potentials (SSEPs) are more easily obtained than transcranial motor-evoked potentials (TcMEPs) in children younger than 6 years. We tested this assumption and the assumption that motor-evoked potentials are rarely obtained in children younger than 2 years. METHODS: The records of all patients who were monitored during surgical procedures between April 1, 2010, and June 30, 2013, were reviewed and those who were younger than 72 months at the time of surgery were identified and analyzed for the rate of obtaining clinically useful SSEPs and motor-evoked potentials. Subgroup analysis was performed by age. RESULTS: A total of 146 patients were identified, 9 had SSEPs without TcMEPs monitored, 117 had both TcMEPs and SSEPs monitored, and the remainder had only electromyographic monitoring. All patients who were to have TcMEPs recorded received a total IV anesthetic. Among the 117 patients who had both SSEPs and TcMEPs monitored, clinically relevant TcMEPs were obtained more frequently than SSEPs (110/117 vs 89/117; χ 2 = 14.82; P = 0.00012). There were significant differences between the rates of obtaining SSEPs and TcMEPs in the 0- to 23-month ( P = 0.0038) and 24- to 47-month ( P = 0.0056) age groups. Utilization of a double-train stimulation technique facilitated obtaining TcMEPs in the youngest patients. CONCLUSIONS: TcMEPs can be obtained more easily than SSEPs in patients younger than 72 months if a permissive anesthetic technique is used. The success rate for obtaining TcMEPs can be further enhanced by the use of a temporal facilitation (double-train) stimulation technique. Abstract : Published ahead of print October 29, 2015